Analisis Respon Konsumen terhadap Strategi Penetapan Harga Bahan Baku UMKM Halal Mart dalam Menghadapi Kenaikan Harga Bahan Baku - Alvina Nurhidayah; Dwi Riyanti; Salsabilah Nur; Yeni Samri Juliati Nst (Universitas 45 Surabaya, 2025)
The halal mart shop is the object of this research which is located at the Ulama Council, Jalan, Gaharu, East Medan, Medan City, North Sumatra 20233. In order to keep up with market developments that are constantly changing and in order to increase success in business in order to achieve goals. Therefore A problem formulation was taken, including: (1) what is the general impression of consumers regarding the quality of halal mart shop products(2) what is the description of the location, prices and services available at halal mart. The method used in this research was a survey with a questionnaire distributed to Halal Mart consumers in Medan.From this analysis it can be concluded: (1) what is the general impression of consumers regarding the quality of halal mart shop products? Some respondents stated that the quality at Halal Mart was comparable to other shops and some stated that the quality was good.(2) What is the description of the location, prices and services at the halal mart? Most respondents considered that the prices set by the halal mart were in line with market prices, although some consumers admitted that they would switch to another shop if the prices at the halal mart were higher, as well as the location. quite strategic, the service is also very good.It was concluded that (1) Halal Mart needs to maintain competitive pricing and pay attention to product quality to attract and retain consumers (2) Halal Mart stores complement the products they sell (3) Halal Mart stores must pay attention to prices in other stores. cheap (4) giving discounts to regular consumers (5) increasing the friendliness of service so that it is more attractive for consumers to shop.This research provides recommendations for Halal Mart to be more sensitive to consumer desires and consider appropriate promotional strategies in order to compete in the market..